POTENSI HIBRID GOLD NANOPARTICLES DAN ANTIBIOTIK VANKOMISIN UNTUK MENGATASI MULTI DRUG RESISTANT BACTERIA (MDR) - Nur Hikmatul Auliya; Ajeng Dian Pertiwi; Edy Kurniawan (Politeknik Medica Farma Husada Mataram, 2019)
Antibiotic-resistant bacteria are responsible for the majority of infections worldwide. The ?-Lactam antibiotics work by inhibiting penicillin-binding proteins (PBPs) which are currently resistant to MRSA (Methicillin-Resistant Staphylococcus aureus). To solve this problem, drug delivery systems methods should be developed to overcome bacterial resistance. Nanoparticles offer a system which can improve bioavailability, efficacy, and specificity works by pharmaceutical drugs. In this study, hybridization between gold nanoparticles and vancomycin antibiotics was carried out followed by the characterization of hybrid by FT-IR and UV-Vis determination. Antibacterial activity testing also was done by the Kirby-Bauer method. The results showed that the vancomycin was resistance against MRSA, whereas hybridization process by gold nanoparticles increased its ability. The hybrid showed antibacterial activity against MRSA. The test showed the ability of hybrid to inhibit MRSA at the concentration of 100 ppm, 500 ppm and 1000 ppm with a clear zone of 13 mm, 24 mm and 28 mm respectively.